A Day Saved is a Life Saved: Direct Antimicrobial Susceptibility Testing from Positively Flagged Blood Culture Bottles and their Concordance with the Routine Method - Aggarwal, Alisha; Abhishek, Kumar S.; Tak, Vibhor; Mehrotra, Sukanya; Nag, Venkat G.; Jain, Vidhi (Infectious Disorders - Drug Targets, 2024)
Background: Sepsis is a major health problem worldwide and is associated with high morbidity and mortality with every hour delay in initiation of therapy. A conventional method of blood culture and Antimicrobial Susceptibility Testing (AST) takes around 48-72 hours. Empirical antibiotics need to be administered until the sensitivity report is made available. It has been estimated that 20-50% of the empirical antibiotics are inappropriate, resulting in prolonged hospital stays, adverse effects, and emergence of drug resistance. Additionally, this also puts an extra financial burden on both the patients and healthcare settings. Performing direct Antimicrobial Sensitivity Testing (dAST) is an important tool to reduce turn-around time (TAT) by at least 18-24 hours, thus reducing morbidity and mortality among critically ill patients. Methods: Direct AST (dAST) was performed from the positively flagged blood culture bottles received between December, 2021 to May, 2022 from Intensive Care Units (ICUs) on Mueller- Hinton Agar (MHA) using four drops of withdrawn blood. dAST was performed for six drugs: Ceftriaxone-30 μg (CTR), Piperacillin/Tazobactam-100/10 μg (PIT), Meropenem-10 μg (MRP), Ciprofloxacin-5 μg (CIP), Aztreonam-30 μg (AT), and Colistin (CL). The zone of inhibition was interpreted as per CLSI M100 ed32, 2022 guidelines. A parallel conventional method was also performed to examine for categorical agreement and disagreement. Identification was carried out using MALDI-TOF MS from the colonies that appeared on the dAST plate on the subsequent day. Results: A total of 162 positively flagged blood culture bottles were included in the study. The majority of the Gram-negative organisms were from Enterobacterales (n=109), followed by Acinetobacter spp. (n=28) and Pseudomonas aeruginosa (n=25). Out of the 972 isolate-antimicrobial combinations, overall Categorical Agreement (CA) was seen in 936 (96.3%), whereas disagreement was observed in 36 with minor error (mE) in 21 (2.2%), major error (ME) in 7 (0.7%), and very major error (VME) in 8 (0.8%) when compared to the routine method. Categorical agreement (CA) of > 99% was seen in ceftriaxone (CTR) and ciprofloxacin (CIP). In comparison, the lowest CA was observed with meropenem (MRP) at 92%. Colistin dAST was performed using the E-strip method, and the result obtained was highly convincing, with an overall disagreement of only 1.2%. Conclusion: Rapid dAST from positively flagged blood culture bottles proved to significantly reduce the TAT from the time of sample collection to the first availability of antimicrobial susceptibility report with excellent categorical agreement of > 95% using the conventional disc diffusion method. Results obtained were within the acceptance criteria set by U. S. Food and Drug Administration (FDA) guidelines of > 90% categorical agreement for a new method. We were able to obtain excellent concordance for colistin using the E-strip method. Performing dAST not only saves a “day”, but its proper implementation would save a “life”.
Keywords: Sepsis